New Approach Methodologies: Physiological responses of daphnids to pharmaceutical mixtures - Emma Rowan; Anne Leung; Katie O’Rourke; Xiaofei Yin; Lorraine Brennan; Konstantinos Grintzalis (Journal of Hazardous Materials Letters)
Conventional methods for water monitoring are insufficient to capture the impacts of pollution because of their sensitivity limits, while they also fail to provide mechanistic insight regarding the actions of pollutants. On the other hand, New Approach Methodologies are more and more introduced as supplementary tools that provide sensitive metrics for pollution assessment. In this context, freshwater sentinel species commonly known as water fleas were used to assess the impact of a pharmaceutical mixture. The pharmaceutical cocktail comprised of representatives of commonly encountered pharmaceuticals and specifically diclofenac, metformin, gabapentin, amoxicillin, trimethoprim, and erythromycin. Combining toxicity, phenotypic and molecular endpoints, results showed differences in mortality, feeding, key enzyme activities and metabolic perturbations, thus supporting a distinct pattern in physiological responses of daphnids that could be used to monitor and predict pollution early.